Identification of TRAPPC9 and BAIAP2 Gene Polymorphisms and Their Association With Fat Deposition-Related Traits in Hu Sheep - Cui, Panpan; Wang, Weimin; Zhang, Deyin; Li, Chong; Huang, Yongliang; Ma, Zongwu; Wang, Xiaojuan; Zhao, Liming; Zhang, Yukun; Yang, Xiaobin; Xu, Dan; Cheng, Jiangbo; et al. (Frontiers in Veterinary Science, 2022)
Fat deposition is an important economic trait that is closely related to feed efficiency and carcass performance in livestock. In this study, the fat deposition-related traits of 1,293 Hu sheep were measured and descriptive statistical analysis was conducted. The results showed that the coefficient of variation of all fat deposition-related traits was higher than 24%. In addition, single nucleotide polymorphisms and the expression characteristics of TRAPPC9 (encoding trafficking protein particle complex subunit 9) and BAIAP2 (encoding brain-specific Angiogenesis inhibitor 1-associated protein 2) genes in Hu sheep were detected using PCR amplification, Sanger sequencing, KASPar genotyping, and quantitative real-time reverse transcription PCR (qRT-PCR). The associations between SNPs and fat deposition-related traits were also analyzed. Two intronic mutations, TRAPPC9 g.57654 A > G and BAIAP2 g.46061 C > T, were identified in Hu sheep. The result of association analysis showed that TRAPPC9 g.57654 A > G and BAIAP2 g.46061 C > T were both significantly associated with the weight of tail fat, tail fat relative weight (body weight), and tail fat relative weight (carcass) (P < 0.05). Comprehensive effects analysis showed that there were significant differences between the combined genotypes and tail fat and perirenal fat deposition. Moreover, qRT-PCR analysis showed that TRAPPC9 and BAIAP2 are widely expressed, and their expression levels were significantly higher in the small-tail group compared with those in the big-tail group (P < 0.01). These results provided important candidate molecular markers that could be used in strategies to reduce tail fat deposition in Hu sheep.